Evolution of gastroesophageal reflux disease symptoms after bariatric surgery: A dose–response meta-analysis - Abdel-Naser Elzouki (9376853) (2022)
Background Obesity is associated with increased prevalence of gastroesophageal reflux disease, with recent reports suggesting improvement in gastroesophageal reflux disease symptoms and weight loss following bariatric surgical intervention. However, the exact impact of the type of bariatric surgery on the evolution of gastroesophageal reflux disease symptoms has remained unexamined. Methods We systematically searched electronic databases (PubMed, EMBASE, Web of Science, and the Cochrane Library from inception to December 2018) for eligible studies that satisfy prespecified inclusion criteria. We included clinical trials of all designs that reported on gastroesophageal reflux disease outcomes following laparoscopic sleeve gastrectomy or laparoscopic Roux-en-Y gastric bypass. Two independent reviewers extracted relevant data based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. Data were pooled using a random-effects model. Main outcomes were symptomatic improvement in gastroesophageal reflux disease symptoms following bariatric surgery. Results A total of 31 studies were analyzed, and a robust-error meta-regression model was used to conduct a dose–response meta-analysis synthesizing data on 31 studies that reported gastroesophageal reflux disease outcomes after bariatric surgery. Of 5,295 patients who underwent either laparoscopic sleeve gastrectomy (n = 4,715 patients) or laparoscopic Roux-en-Y gastric bypass (n = 580 patients), 63.4% experienced improvement in gastroesophageal reflux disease symptoms (95% CI 32.46–72.18). The dose–response meta-analysis demonstrated a window period of 2 years for sustained improvement after which symptoms began to recur in those that were asymptomatic. Conclusion Bariatric surgery may improve gastroesophageal reflux disease symptoms in obese patients who underwent laparoscopic sleeve gastrectomy; however, the most favorable effect is likely to be found after Roux-en-Y gastric bypass surgery. The effects were not sustained and returned to baseline within 4 years. Other Information Published in: Surgery Open Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.sopen.2021.11.006